Prediction of the two-tone suppression and intermodulation performance of auditory systems - Abuelma’atti, M.T. (2006)
Using a model based on subcritical Hopf amplifiers, closed form expressions are obtained for two-tone suppression and the third-order intermodulation performance of the human auditory system. The proposed model approximates the Hopf amplifier characteristic using Fourier-series expansion. The parameters of the Fourier-series approximation can be easily obtained without recourse to sophisticated curve-fitting techniques. The results are compared with previously reported observations.